2008
DOI: 10.1017/s1368980007000055
|View full text |Cite
|
Sign up to set email alerts
|

Energy costs of daily activities for women in rural India

Abstract: Objective: In view of the paucity of data on energy costs, the present study aimed to estimate these for typical daily activities performed by women in rural India. Design: A cross-sectional study covering 26 different activities was done by indirect calorimetry using the Oxylog TM instrument (Morgan). Settings: Villages about 30-40 km from Pune city, Maharashtra, India. Subjects: Energy costs were measured on 22 rural Indian women aged 18-45 years. Results: Irrespective of whether an activity was domestic or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 33 publications
3
13
1
Order By: Relevance
“…[50] Data from the current study also suggest that concerns of limited generalizability are unwarranted. For example, similar values were found for BMR in the current study (0.86 kcal/kg/hr) compared to others (0.84–0.99 kcal/kg/hr) [25][27], [39], [41]. Finally, we used MET units and energy expenditure per kg of total body weight to account for weight differences.…”
Section: Discussionsupporting
confidence: 72%
“…[50] Data from the current study also suggest that concerns of limited generalizability are unwarranted. For example, similar values were found for BMR in the current study (0.86 kcal/kg/hr) compared to others (0.84–0.99 kcal/kg/hr) [25][27], [39], [41]. Finally, we used MET units and energy expenditure per kg of total body weight to account for weight differences.…”
Section: Discussionsupporting
confidence: 72%
“…Activity levels reported for both urban and rural men were lower than those reported in a study from Cameroon although comparable for women [41], who also showed consistent levels with a previous study from rural India [38]. Lower levels of total activity in urban areas have been noted in other studies in both north [2] and south India where PA was negatively associated with level of urbanisation for both men and women [43].…”
Section: Discussionsupporting
confidence: 85%
“…Previous research on PA within India has tended to focus on specific geographic locations or sub-groups, using different methods to quantify PA and has not attempted to examine differences between migrants and other groups [35], [36], [37], [38]. The higher levels of activity seen amongst rural participants compared to migrant and urban residents within this study are however concordant with previously published migration study data from other LMIC [39].…”
Section: Discussionsupporting
confidence: 83%
“…Eleven studies related female employment in agriculture to women's energy expenditure and their nutrition and health outcomes . Papers attempted to classify the energy costs of daily household and farming activities; to assess adaptations to seasonality; to assess the impact of activity and food intake on neonatal size; and to look at differences in thinness according to work behavior and gender.…”
Section: Pathway 6: Women In Agriculture and Maternal Nutrition And Hmentioning
confidence: 99%